A doublet pair drop and dribble - Bacić, Cica Z (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2019)
The paper deals with the content relations of the nouns drop and dribble in order to see whether they are equal or point to each other, more precisely, the possible duplicity or synonymity of this pair is examined. In order to get answers to specific questions, we will analyze the creative aspect by historical review, we will examine what kind of status they have in the language manuals, as they are explained and processed in dictionaries. Then the frequency in practice is investigated on the basis of the Corpus of the Faculty of Mathematics. Likewise, our goal is to determine whether the collocation components are synonymous, and finally, we are discussing the possibilities of overcoming them, and investigating which solution has the advantage over the other.